De novo activating epidermal growth factor mutations (EGFR) in small‐cell lung cancer. Issue 9 (September 2017) - Thai, Alesha; Chia, Puey L.; Russell, Prudence A.; Do, Hongdo; Dobrovic, Alex; Mitchell, Paul; John, Thomas
Abstract: In Australia, mutations in epidermal growth factor mutations ( EGFR ) occur in 15% of patients diagnosed with non‐small‐cell lung cancer and are found with higher frequency in female, non‐smokers of Asian ethnicity. Activating mutations in the EGFR gene are rarely described in SCLC. We present two cases of de novo EGFR mutations in patients with SCLC detected in tissue and in plasma cell free DNA, both of whom were of Asian ethnicity and never‐smokers. These two cases add to the growing body of evidence suggesting that screening for EGFR mutations in SCLC should be considered in patients with specific clinical features.